Peran Media Komunikasi pada Keluarga Long Distance Marriage (Studi pada Mahasiswa PPDS FK UNAND) - santhiana surya; Ernita Arif; Asrinaldi Asrinaldi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The marriage is essentially a sacred bond and will last a lifetime. A marriage not only brings together two individuals but also brings together two families who will contain a new family system. In the present we have not seen a few families who underwent a long distance marriage and there are many factors that influence, there are those who have to make a living far to his family or some who continue their school. This research aims to see how the role of communication media and the quality of communication in the family live a long distance. This research is a qualitative research, data collection is done by the method of semi-structured interviews to find this research informant using the snowball technique. In this study there are two concepts, namely family communication and family communication media which results from this study are communication media playing an important role in doing a long distance marriage because the foundation of a long distance relationship commitment is communication that never breaks. All informants in this study argue that video call communication media are the best media used because we can meet face to face even though the body does not meet.